1988
DOI: 10.1159/000199767
|View full text |Cite
|
Sign up to set email alerts
|

New Canine Model of Chronic Pancreatitis due to Chronic Ischemia with Incomplete Pancreatic Duct Obstruction

Abstract: A new experimental model of chronic pancreatitis was produced by a combination of chronic ischemia and incomplete obstruction of the pancreatic duct. Ischemia was induced by ligation and separation of branches flowing into the left pancreatic lobe from the splenic artery. Incomplete ductal obstruction was achieved by ligation and separation of the minor pancreatic duct and placement of a polyethylene tube in the major pancreatic duct. Macroscopic examination at 6 months after model preparation showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…Complete PDL and partial PDL have been used for decades as models for acute and chronic pancreatitis in humans (9,10). Compared with complete PDL, the partial PDL model has several advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete PDL and partial PDL have been used for decades as models for acute and chronic pancreatitis in humans (9,10). Compared with complete PDL, the partial PDL model has several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PDL induces robust pancreatitis through ductal occlusion, which may mimic the pathogenesis of pancreatitis in many humans. Third, acute pancreatitis by PDL progresses to chronic pancreatitis relatively quickly, which not only significantly shortens the experimental period but also allows easier detection of changes in the parameters of interest (911,4143). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em cães, a ligadura de ramos da artéria esplênica contribui para a indução de pancreatite crônica 23 , mas protege o animal de infecção por pneumococo, quando associada à exérese do pólo inferior do baço 24 . A ligadura da artéria esplênica em coelhos diminui a resposta imune à administração intravenosa de antígenos morfologicamente modelados 25 .…”
Section: Introductionunclassified
“…Earlier, we have reported that a combination of persistent paren chymal cell damage and pancreatic duct obstruction is important in producing a CP model (combination theory) [4], Clinically, various etiological factors including alco hol intake are recognized, but the pathophysiology of CP still remains obscure. Based on our investigations, we con sider ischemia as an important factor in the pathogenesis of CP [5], We reported the usefulness of our experimental CP model due to chronic ischemia with incomplete pan creatic duct obstruction [4], In this study, we investigated the change in exocrine pancreatic function and the histopathological findings in our model of CP due to chronic ischemia.…”
mentioning
confidence: 99%